The influence of cobalt on the growth rate of artificially fed mullet (Mugil spp.) spawn - preliminary data - Ioniță, Reveica; Boghici, Viorica (Cercetări Marine - Recherches Marines, 2026)
Results of laboratory experiments concerning administration of cobalt in the food of grey mullet (Mugil spp.) spawn are presented. The achieved growth rate differs by a 14% increment from that of the witness.